Developing early morning flowering version of rice variety CO 51 to mitigate the heat-induced yield loss - Ayyenar, Bharathi; Kambale, Rohit; Duraialagaraja, Sudhakar; Manickam, Sudha; Mohanavel, Vignesh; Shanmugavel, Priyanka; Alagarsamy, Senthil; Ishimaru, Tsutomu; Jagadish, Krishna S.V.; Geethalakshmi, Vellingiri; Muthurajan, Raveendran (MDPI, 2023)
By 2050, the rice production needs to be increased by at least 50% in order to meet the growing food demands of the global population. Among various yield limiting factors, high temperature is fast becoming a major threat to sustain rice yields due to its increased frequency of occurrence and severity of stress events. The development of heat-resilient rice cultivars has been slow due to the lack of relevant donors for heat tolerance traits and limited information regarding the genetic basis of these component traits. The early morning flowering (EMF) trait, contributing to heat escape by promoting flowering/anthesis during cooler hours in the morning is demonstrated to offer protection against high-temperature-induced failure of pollination and fertilization. In this study, evaluation of CO 51, IR64 and IR64-qEMF3 (NIL of IR64 harboring QTL promoting EMF revealed that qEMF3 promoted early morning flowering in IR64-qEMF3 (1½ to 2 h earlier than IR64) and thereby reduced the sterility by about 8.15%. Attempts through marker-assisted backcross breeding led to development of advanced backcross progenies (NILs) of CO 51, harboring qEMF3. Evaluation of 88 BC3F2 progenies identified 19 progenies harboring qEMF3 under homozygous conditions. Evaluation of NILs of CO 51 harboring qEMF3 during summer 2019 revealed that the NILs exhibited early (7.30 a.m.) onset of anthesis by 1½ h and completed its peak anthesis well around cooler hours (9.30 a.m.) of the day and thereby recorded reduced spikelet sterility (7.8–9.0%) than their recurrent parent CO 51 (19.2%). The current study clearly demonstrated the efficacy of early morning flowering in the mitigation of yield losses under high-temperature conditions in a farmer preferred rice variety.